Range findings of lethal concentration of zinc oxide nanoparticles (ZnO NPs) to juvenile red tilapia - Mohd Azni, Mohamad Fazwan Afiq; Wan Johari, Wan Lutfi; Mohamad Zaid, Siti Sarah; Mohd Daud, Hassan (Hibiscus Publisher, 2023)
Zinc oxide nanoparticles (ZnO NPs) have attracted increasing concerns because of their unique properties and widespread applications in industry, which may adversely impact not only specific ecosystems but also human health. Although numerous studies have investigated the influence of ZnO on fish, there is a paucity of information available regarding the LC50 value of ZnO NPs and effects of ZnO NPs on physical and behavioural of red tilapia Oreochromis sp., which are a vital fish-producing species in Malaysia. In this study, the effects of acute exposure of ZnO NPs (30-50 nm) were conducted in red juvenile tilapia fish (Oreochromis sp.) consisting: i) the assessment of the concentration-response curves and median lethal concentration (LC50) at 96 hours (4 days); and ii) evaluating the toxicity effects of ZnO NPs exposure on red tilapia based on the LC50 at 96 hours by observing behavioral and physical changes. 10 juvenile fish in each tank were exposed in the static non-renewable test solution for 96 hour (4 days). The LC50 value of ZnO NPs was 80.326 mg/L after 96 h of exposure. Physical and behavioral alterations were observed, including changes in swimming patterns, buoyancy control, ventilation, aggression, and appearance. Generally, red tilapia at higher concentrations exhibited dense schooling behavior, loss of buoyancy control, lethargy, movement in water, hypo- and hyperventilation, frequent gulping at the surface of the water, and increased aggression towards cannibalism. However, the colour of fish skin from each concentration does not show any changes observed to the fish along the 96-hours period of study.